Pemberdayaan Juru Pelihara Cagar Budaya Sebagai Upaya Pelestarian Objek Wisata Sejarah Di Aceh - Irwan, Irwan; Nur, Muhammad; Fitriani, Fitriani; Fatianda, Septian; Hasanah, Ida; Agustina, Lisa; Rumaida, Rumaida; Maulida, Cut Nyak Meutia (Jurnal Community, 2025)
Aceh is an area that has a lot of historical heritage in the form of cultural heritage sites. The problem that occurs now is that there are so many cultural heritage sites that are not maintained. One way to care for them is by placing a caretaker in charge of maintaining and preserving the site. The purpose of the research is to examine the concept of empowerment carried out by the government towards cultural heritage and how the role and duties of this caretaker. This research uses qualitative motede with descriptive analysis approach. Data sources were obtained from literature studies, field observations, and direct interviews with the CPC and the caretakers at the Indrapatra fort site, Sultan Iskadar Muda fort, Inong Balee Fort, and Kandang XII Tomb. The results showed that the BPK has placed 83 caretakers in several cultural heritage sites that have been recorded. The empowerment strategy carried out is to provide capacity building training once a year, provide salary wages according to the provisions, and evaluate and monitor the performance of the stewards. The duties and roles of these stewards are to maintain, care for, clean, and guide visitors who come to the cultural heritage site